Avaliação das condições hidromorfológicas do Riacho Guaraíra - PB pelo método Bávaro - Silva, Alexandre Ferreira da (2013)
This study aimed to evaluate the stream hydromorphological Guaraíra through the Bavarian method. The basin of the creek is located within the catchment area of Gramame, the southern portion of the state of Paraíba. Therefore, the creek was divided into 47 sections of 100 meters. During the survey of the characteristics of the stream was possible to observe the level of anthropogenic modification along its route. These surveys take into account the dynamics of river and plain and with the junction of the dynamics is obtained modification degree ranging from 1 (no change) to 7 (completely changed), based on the use of the method Bávaro. The creek Guaraíra has 81% of its route unchanged, despite being in a watershed with 33.63% of its area modified crops of sugar cane and pineapple. The 19% change were due to engineering works and, as previously mentioned, sugarcane also influenced this change in the natural state. With the method, it is clear that investments for restoration of local anthropogenic are more effective due to the division of the stream in patches. Thus, save yourself money and time by acting at the core of the problems.